Anaplastic Spindle Cell Squamous Carcinoma Arising from Tall Cell Variant Papillary Carcinoma of the Thyroid Gland: A Case Report and Review of the Literature - Darren K. Patten; Alia Ahmed; Owain Greaves; Roberto Dina; Rashpal Flora; Neil Tolley (Case Reports in Endocrinology)
Tall cell variant (TCV) of papillary thyroid carcinoma (PTC), an aggressive form of thyroid cancer, is characterised by 50% of cells with height that is three times greater than the width. Very rarely, some of these cancers can progress to spindle cell squamous carcinoma (SCSC) resulting in cancers with elements of both SCSC and TCV PTC. Here we report a case of SCSC arising from TCV PTC. In addition to this case, we have performed a literature review and compiled all published reports of SCSC arising from TCV PTC, including the nature of treatment and the prognosis for each of the 20 patients recorded. This is intended for use as a guide for clinicians in what the most appropriate treatment options may be for a newly diagnosed patient. Due to the rarity coupled with diagnosis occurring at a very advanced stage of disease progression, performing clinical trials is difficult and therefore drawing conclusions on optimal treatment methods remains a challenge.